Marketing Mix Strategy On Marketing Performance And Company Performance In The Business Environment As Moderating Variables (Study on: Small and Medium Seaweed Industry Players in Bontang City) - M Risal (Indonesian Journal Economic Review (IJER), 2025)
This study examines marketing strategies that include the implementation of marketing performance and company performance that moderates external environment. In this study, which includes the application of marketing strategies which include product strategies, price strategies, distribution strategies, promotion strategies, (4Ps), while marketing performance includes adaptation, effectiveness, and efficiency, company performance includes technological innovation, marketing capabilities, and financial performance while environmental moderation includes competition between industries, the threat of foreign industry entry, and supplier bargaining power. The type of research used is a descriptive method and uses a causality method using path analysis. The number of populations and samples was used by survey methods and cluster proportional sampling methods. Data was collected from the population of 9 small and medium industries with a total of 115 employees. The results of the test were carried out using Partial Least Square (PLS), the results of each variable were measured, namely; marketing strategy 0.275 with the medium category, the competition environment variable 0.400 with the strong category, while the company performance variable 0, was categorized as weak. Furthermore, the relationship between marketing strategy and marketing performance has a positive and significant influence with a value of 0.846 and a P-Value of 0.000, the relationship between marketing strategy and company performance has a positive and significant influence with a value of 0.846 and a P-Value of 0.002, the relationship between marketing performance and company performance does not have a positive but significant influence with a value of 0.203 and a P-Value of 0.141 on MSMEs and SMEs in the seaweed industry in Bontang City.